Pengaruh Pemberian Aromatherapy terhadap Stres yang Dirasakan Mahasiswa yang Sedang Mengerjakan Skripsi - Manikasanti, Ni Putu Sartika; Setiasih, Setiasih; Yuwanto, Listyo (Universitas Muhammadiyah Metro, 2024)
In this study, we explain the effect of aromatherapy on stress of students who are working on thesis. This experimental research using a pretest and posttest control group design. This study was implemented in 15 student who randomly allocated into 2 groups through a random assignment process. Prior to the experiment, the participants were given stress induction. The control group was given treatment using a mixture of toner and water with a ratio of 1:4 which was inhaled using a diffuser. The experimental group received treatment using lavender essential oil. In this study, hypothesis testing was conducted using independent samples t-test and paired samples t-test. Based on the results of the hypothesis test that is not significant (p = 0.858), this shows that there is no difference between the results of the pretest and post-test. In this study, the experimental group (mean = -13.500) and the control group (mean = -14.571) experienced a decrease. The decrease that occurred in the control group was influenced by participants beliefs regarding the aromatherapy used, which could lead to a placebo effect or